Physicochemical, structure and functional characteristics of Tacca leontopetaloides starches grown in Indonesia - DIODE YONATA; PRIYANTO TRIWITONO; LILY ARSANTI LESTARI; YUDI PRANOTO (Society for Indonesian Biodiversity, 2023)
Abstract. Yonata D, Triwitono P, Lestari LA, Pranoto Y. 2023. Physicochemical, structure and functional characteristics of Tacca leontopetaloides starches grown in Indonesia. Biodiversitas 24: 6396-6406. Understanding the physicochemical, structure and functional characteristics of tacca tuber (Tacca leontopetaloides) starch is crucial as a scientific basis for its development, especially in the food industry. Despite the abundance of starch in Indonesian tacca tubers, its potential remains largely untapped. This research aims to determine the physicochemical, structure and functional characteristics of tacca tuber starch from three different regions in Indonesia: Bangkalan, Garut and Sumenep. Wet extraction yielded tacca tuber starch with yields ranging from 21.26 to 26.42%. Significant differences (p<0.05) were observed in proximate composition (ash, lipid, and protein), starch purity (97.35-98.48%), amylose content (32.81-35.26%), and functional properties like swelling power (9.67-10.51 g/g at 95°C), solubility (4.93-5.87% at 95°C), water holding capacity (0.77-0.90 g/g), oil holding capacity (0.62-0.71 g/g), and relative crystallinity (24.22-27.03%). Thermal properties and pasting properties (except breakdown viscosity) exhibited significant variations. The gelatinization temperature profile of tacca tuber starch ranged from 57.92 to 76.38°C, with an ?H value of around 3.81-4.62 J/g. Meanwhile, the temperature of tacca tuber starch paste ranged from 72.12 to 72.88°C. Tacca tuber starch granules are polygonal, elliptical, oval to slightly ellipsoidal, with an average granule diameter of 20.21-40.43 ?m. Based on the X-ray diffraction pattern, tacca tuber starch shows the CA-type, containing orthorhombic and hexagonal structure crystals. Tacca tuber starch has a high lightness (92.01-93.62) and whiteness index (91.68-92.74). In conclusion, the cultivation location significantly influences the physicochemical, structural, and functional characteristics of tacca tuber starch.